Comparing the effect of ICT and longhand note-taking instructions towards learners’ comprehension test results - Clara Herlina Karjo (Universitas Katolik Indonesia Atma Jaya, 2018)
With the advancement of technology nowadays, taking notes by hand seems old-fashioned to most students nowadays. They prefer typing using their various gadgets since it will be done faster, especially when there is a lot of information to be recorded. However, the use of ICT devices (such as laptops, smartphones, and tablets) in the classroom has a tendency to be distracting for the students – it is very easy for the students to take out their gadgets and click on Facebook or other applications during a dull lecture. The purpose of the present study is to find out whether note-taking using ICT devices affect the students’ understanding of the lecture. This study will use a quasi-experimental design, with 52 English department students of a private university as the participants. They will be divided into two groups as the control and experimental group. Participants of both groups were instructed to watch a video from TED talks twice. While watching the video, the control group was instructed to take notes by hand, while the other group was instructed to take notes using their various devices. After that, participants had to do a comprehension test of the lecture video. The results revealed that participants who took notes by handwriting performed better in comprehension test compared to those who took notes using ICT devices.